Costs of an exergame intervention for patients with heart failure. (3rd October 2022) - Klompstra, L; Mourad, G; Jaarsma, T; Stromberg, A; Alwin, J
Abstract: Background: Exergaming is promising for patients with heart failure who are less inclined to start or maintain exercise programmes involving traditional modes of physical activity. It is important to gain insights into aspects related to costs to in order to compare with other costs for rehabilitation and make priorities. Purpose: To gain insights into aspects related to the costs of an exergame intervention for patients with heart failure and their willingness to pay for such an intervention. Method: In a randomised controlled trial, the HF-Wii study, the intervention group (n=305) received an introduction to the exergame, the exergame was installed at home and technical and practical support was available when needed for three months. Patients received telephone follow-ups after the installation. The control group (n=300) received activity advice and telephone follow-ups. We collected data on hospital use and costs, costs of the exergame intervention, patient time-related costs and conducted interviews to establish willingness to pay in a subset of patients. Results: No significant differences were found between the exergame group (n=300) vs. the control group (n=305) in hospital use or costs (one-year number of hospitalisations p=0.60, costs p=0.73). The cost of the intervention was 190 Euros, and the patient time-related costs were 98 Euros (see Table 1). Of the total estimated costs for the intervention, 288 Euros, patients were willing to pay, on average, 58%. Satisfaction level regarding the exergame intervention was significantly correlated with patients' willingness to pay (rs=0.47, p=0.01). Conclusion: Although the costs of developing a exergame can be high, this study shows that the cost for the implementation of exergaming in an individual for practice was only 288 Euro per patient. Patients were willing to pay more than half of the exergame intervention and patients with higher satisfaction levels were willing to pay more than those with lower satisfaction levels. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish National Science Council